KNOWLEDGE MANAGEMENT SYSTEM PROVISIONS ON THE IMPORT OF CONSIGNMENTS AT CUSTOMS AND EXCISE SUPERVISION AND SERVICE OFFICE PASAR BARU - Tri Cendekia Dewi; Syaifudin Abdullah; Teddy Siswanto (Intelmatics, 2021)
The activity of importing goods has the potential to experience obstacles or problems in the processing through Customs and Excise due to various kinds of requirements that must be met. So that knowledge management is needed by importers who will carry out import activities because it can increase knowledge in the process and delivery requirements. In order to maximize knowledge, efforts need to be made to create a website-based knowledge management system that is expected to be a solution to these needs. The method used in this study is the Becerra-Fernandez framework method for data collection and processing in determining knowledge management solutions. It also uses the waterfall method for system development using the System Development Life Cycle (SDLC) approach.